2010
DOI: 10.3844/ajabssp.2010.370.375
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Inositol on Growth, Feed Utilization and Blood Biochemical Parameters for Juvenile Barramundi (<i>Lates calcarifer</i> Bloch)

Abstract: Problem statement: The utilization of inositol was detected for growth performance and erum biochemical parameters of juvenile barramundi (Lates calcarifer). Approach: A 56 day feeding trial was conducted to evaluate the effect of inositol on growth, feed utilization and serum biochemical parameters for juvenile barramundi Lates calcarifer (initial size 5.51±0.07g). Six experimental fish meal-based isonitrogenous (42% crude protein) and isolipidic (10% crude lipid) diets containing levels of inositol (350, 364… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
6
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
6
6
2
Order By: Relevance
“…These results agreed with Diao et al. () for Barramundi, which showed a similar tendency between serum TP and dietary MI supplementation, but did not agree with Waagbø et al. () for Atlantic salmon, which reported that serum TP correlated negatively with dietary MI supplementation.…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…These results agreed with Diao et al. () for Barramundi, which showed a similar tendency between serum TP and dietary MI supplementation, but did not agree with Waagbø et al. () for Atlantic salmon, which reported that serum TP correlated negatively with dietary MI supplementation.…”
Section: Discussionsupporting
confidence: 65%
“…In addition, Diao et al. () reported that MI could increase the serum TP of barramundi. In Jian carp, enhancement of non‐specific immune response by MI might be principally associated with improvement of lysozyme activity and phagocytic activity of leucocyte (Jiang et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations